Humic Substances: Bridging Ecology and Agriculture for a Greener Future - Angela Maffia; Mariateresa Oliva; Federica Marra; Carmelo Mallamaci; Serenella Nardi; Adele Muscolo (Agronomy)
Humic substances (HSs) are emerging as multifunctional natural catalysts in sustainable agriculture, offering novel opportunities to enhance soil health, plant productivity, and environmental resilience. This review synthesizes recent insights into the chemical diversity, biological mechanisms, and ecological impacts of HSs, presenting a new perspective on their role as dynamic agents in agroecosystems. Derived from decomposed organic matter, HSs regulate critical processes such as nutrient cycling, carbon sequestration, and pollutant detoxification. Unlike plant and microbial biomass, which undergo rapid mineralization due to their active dynamism, HSs exhibit significant resistance to biodegradation, leading to a prolonged residence time in soil that spans years or even centuries. This stability allows HSs to maintain their functional roles over extended periods, contributing to long-term soil health and ecosystem sustainability. Their integration into agricultural systems has demonstrated profound effects, including improved soil structure, increased water retention, and the stimulation of microbial activity, which collectively bolster plant stress tolerance and yield. Notably, it has been proposed that HSs exhibit hormone-like properties, influencing plant signaling pathways to enhance root architecture and nutrient acquisition. Moreover, HSs contribute to environmental remediation by regulating the leaching of heavy metals, mitigating nutrient runoff, and fostering climate resilience. This review highlights the synergistic potential of combining HSs with organic amendments like compost and biochar, positioning HSs as a cornerstone of regenerative farming practices. Addressing challenges such as variability in composition and application methods, the discussion underscores the urgency of developing standardized approaches to harness their full potential. By framing HSs as versatile and adaptive tools, this review paves the way for advancing sustainable agricultural systems while addressing global challenges like food security and climate change.